STUDY ON BIOMOTRICE CAPACITIES AT THE JUNIOR ATHLETES PRACTICING BASKETBALL (GYMNASIUM, 2017)
Analysis carried out in our study aims to identify the athletes biomotric level at Steaua Basketball juniors U16 and U18 are halfway through training before the competion wanting to identify the effectiveness of the training programs at a specific period and age or if they applied the use of information to obtain an aim of adjusting the parameters of effort and resources used. Actual testing of the study was realised on a total of  37 athletes from basketball practice with experience of at least 2 years and with an average age of 15.6 years and a 1.90 cm height. Three standardized tests were applied to measure the initial speed, total speed, agility and endurance under speed and they are: running speed over a distance of  20 m, T test, and YoYo test. The results and data obtained showed us that we need changes in the training plan aimed at developing speed and agility biomotrice qualities and for resistance to maintain the same characteristics. In conclusion intermediate, testing in performance sport especially juniors, are absolutely necessary thus realizing real feedback on the effectiveness is planned and the sport periodization is made by coaches.